Microcontroller-based Automatic Granule Weighing device with Human Machine Interface (HMI) integration - Valendi, Ihsan Riga; Risfendra (Department of Electrical Engineering Universitas Negeri Padang, 2025)
This research presents the design and development of an automatic granule weighing system based on a microcontroller, integrated with a TFT-based Human Machine Interface (HMI). The system aims to enhance accuracy and efficiency in the weighing process of granular raw materials, particularly in small- to medium-scale industries. It utilizes a load cell sensor and HX711 module for precise weight measurement, a vibrating motor to ensure consistent material flow, and a servo motor to control the dispensing valve. The HMI enables users to set target weights, adjust vibration speed, and monitor real-time data. Testing was conducted using rice granules with three different speed modes (low, medium, and high) and eight target weight variations. The system achieved an average error of 0.676% at low speed, 0.184% at medium speed, and 0.542% at high speed, with an overall accuracy of 99.533%. The integration of automated weighing mechanisms with an intuitive HMI demonstrates the system’s potential for industrial applications requiring precise, reliable, and user-friendly material handling